Influence of TikTok’s Social Media Marketing and Online Consumer Review on Purchasing Decision - Maulana Pratama; Ghia Subagja; Gishella Duta (University of Merdeka Malang, 2023)
The main purpose of the study was to identify the influence of TikTok social media marketing and online consumer review on purchasing decision on Jiniso’s products. Population of this study was college student who used TikTok in Indonesia and had bought Jiniso’s products. The sampling technique used purposive sampling to obtain 300 respondents. The analytical test tool used SmartPLS v.3 with SEM (Structural Equation Model) analysis method. The result of this study indicate that TikTok social media marketing and online consumer review simultaneously had a 52.7% impact on purchasing decision. While the partial test results of each variable showed that social media marketing TikTok had a significant effect on purchasing decisions by 12.7% and online consumer reviews had a significant effect on purchasing decisions bye 63.8%.